The impact of digital payments on the financial vulnerability of rural households: empirical evidence from China - Fan Xu; Lezhu Zhang (Frontiers in Sustainable Food Systems)
IntroductionPoverty eradication is the primary goal of the United Nations 2030 Agenda for Sustainable Development (SDGs). Despite China’s significant achievements in poverty alleviation, many rural households still struggle to maintain a sustainable livelihood may even slip back into poverty due to ineffective risk responses when facing risks and challenges.MethodsThis study employs data from the 2017–2019 China Household Finance Survey to theoretically and empirically examine the impact and mechanisms of digital payments on the financial vulnerability of rural households.ResultsThe study’s results indicate that digital payments significantly reduce the financial vulnerability of rural households, a finding that remains robust even after accounting for endogeneity, employing alternative variable measurement approaches, and conducting propensity score matching tests. Mechanism analysis suggest that encouraging rural households to hold commercial insurance, engage in non-farm employment and expand their family social networks are key pathways by which digital payments impact the financial vulnerability of rural households. Further heterogeneity analyses reveal that digital payment plays a more substantial role in mitigating the financial vulnerability of rural households in the western region, which have low financial assets and high health risks, compared to those in the central and eastern regions, which have high financial assets and low health risks.DiscussionTherefore, this paper suggests that the government should continue to promote the in-depth integration of digital technology and financial services, strengthen the construction of rural digital infrastructure in areas lagging behind in traditional finance, enhance the comprehensive service function of digital payments, and enrich the coping strategies of farmers to mitigate financial vulnerability, while remaining vigilant about the potential consequences of digital payment.